1997
DOI: 10.1128/jb.179.2.417-422.1997
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of mutators in A cell population

Abstract: A Lac؊ strain of Escherichia coli that reverts by the addition of a G to a G-G-G-G-G-G sequence was used to study the proliferation of mutators in a bacterial culture. Selection for the Lac ؉ phenotype, which is greatly stimulated in mismatch repair-deficient strains, results in an increase in the percentage of mutators in the selected population from less than 1 per 100,000 cells to 1 per 200 cells. All the mutators detected were deficient in the mismatch repair system. Mutagenesis results in a similar increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
241
0
5

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(254 citation statements)
references
References 36 publications
8
241
0
5
Order By: Relevance
“…In these circumstances, treatment may result in a cytotoxic response in normal cells with increased resistance to drug treatment due to damage tolerance in tumors that lack MMR activity. Furthermore, analogous to studies observed in bacteria (LeClerc et al, 1996;Mao et al, 1997) MMR-deficient cells could, in fact, be selected for by such DNA-directed FP treatments. In addition, treatment of MMR-deficient tumors may harbor an elevated level of mutation due to FP-induced DNA lesions.…”
Section: Clinical Applicationsmentioning
confidence: 90%
“…In these circumstances, treatment may result in a cytotoxic response in normal cells with increased resistance to drug treatment due to damage tolerance in tumors that lack MMR activity. Furthermore, analogous to studies observed in bacteria (LeClerc et al, 1996;Mao et al, 1997) MMR-deficient cells could, in fact, be selected for by such DNA-directed FP treatments. In addition, treatment of MMR-deficient tumors may harbor an elevated level of mutation due to FP-induced DNA lesions.…”
Section: Clinical Applicationsmentioning
confidence: 90%
“…32. Mutator mutations are deleterious in most conditions (33)(34)(35)(36) and are found at correspondingly low frequencies in laboratory populations of, for instance, E. coli and Salmonella typhimurium (37,38). A general argument suggests that excesses of multiples usually occur The reporter gene is natural unless noted to be a transgene.…”
Section: Widespread Excesses Of Mutants Bearing Multiple Mutationsmentioning
confidence: 99%
“…During long-term adaptation or passage through selective bottlenecks, mutators can arise from a population and outgrow the wild-type strain (15-17). The advantage conferred by mutator genes is indirect because they increase fitness by introducing mutations at other loci that offer selectable growth benefits (14,15).Experiments involving the competition of bacteria with differing mutation rates have generally used only one or a few mutators, have not included antimutators, and have typically entailed pairwise competition. Although mutators often outcompete wild-type strains in serial transfer experiments, theoretical models predict that, as mutation rates increase, a threshold is crossed where hypermutability becomes more deleterious than beneficial (18,19).…”
mentioning
confidence: 99%